Plant Growth Promoting Rhizobacteria (PGPR) Increases Yield and Mineral Contents of Rice by Mobilizing Nutrients in the Rhizosphere (Research in Agriculture Livestock and Fisheries, 2023)
Plant growth-promoting rhizobacteria (PGPR) are multipurpose entities in case of crop quality and yield improvement. This study evaluated the impact of PGPR inoculation in root zone nutrient release, rice yield, and grain nutrient (P, Fe, Mn, and Zn) content in two popular rice varieties of Bangladesh (viz., BRRI dhan49 and Binadhan7). It was a single factor (bacterial treatment) experiment where B0, B1, B2, and B3 treatments represented the inoculated control, indole acetic acid (IAA) producing bacteria consortium, phosphorus solubilizing bacteria (PSB) consortium, and combination of B1 and B2 treatments, respectively. Nutrients released in pore water was higher at 5 days after transplanting (DAT), compared to 25 DAT. Mostly B2 and B3 treatments performed significantly in the number of tillers/pots, straw yield, grain yield, grain P, Mn, Fe content, and all four nutrients uptake. The highest grain yield observed in B3 treatment is in both Binadhan7 (42.10±1.76 g/pot) and BRRI dhan49 (36.20±1.57 g/pot). PSB containing B2 treatment bio-fortified the largest amount of P in both rice varieties. On the other hand, the B3 treatment stored the highest amount of Mn (46.70±1.30 and 44.30±1.37 mg/kg) and Fe (45.30±2.90 and 25.70±2.37 mg/kg) in Binadhan7 and BRRI dhan49, respectively. The B3 treatment resulted in maximum nutrient content (P, Mn, and Fe) and uptake (P, Mn, Fe, and Zn) in both rice varieties. These bacterial isolates seemed promising for rice yield and quality improvement in an eco-friendly and sustainable way.Res. Agric. Livest. Fish. 10(1): 73-81